Asteroids IV 2015
DOI: 10.2458/azu_uapress_9780816532131-ch014
|View full text |Cite
|
Sign up to set email alerts
|

Small Near-Earth Asteroids as a Source of Meteorites

Abstract: __________________________________________________________________________Small asteroids intersecting Earth's orbit can deliver extraterrestrial rocks to the Earth, called meteorites. This process is accompanied by a luminous phenomena in the atmosphere, called bolides or fireballs. Observations of bolides provide pre-atmospheric orbits of meteorites, physical and chemical properties of small asteroids, and the flux (i.e. frequency of impacts) of bodies at the Earth in the centimeter to decameter size range. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
78
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(79 citation statements)
references
References 162 publications
1
78
0
Order By: Relevance
“…Surprisingly, one meteorite was H chondrite, one was LL chondrite and one was LL chondrite with embedded achondritic clast. These findings shed new light on some old meteorite finds, such as the Galim meteorite fall (LL+EH), Hajmah (ureilite+L), Gao-Guenie (H+CR), and Markovka (H+L) (Borovička, Spurný & Brown 2015). Therefore asteroids with mixed mineralogies might be more abundant than previously thought, but their formation mechanism(s) remain mysterious (Horstmann & Bischoff 2014).…”
Section: Introductionmentioning
confidence: 88%
“…Surprisingly, one meteorite was H chondrite, one was LL chondrite and one was LL chondrite with embedded achondritic clast. These findings shed new light on some old meteorite finds, such as the Galim meteorite fall (LL+EH), Hajmah (ureilite+L), Gao-Guenie (H+CR), and Markovka (H+L) (Borovička, Spurný & Brown 2015). Therefore asteroids with mixed mineralogies might be more abundant than previously thought, but their formation mechanism(s) remain mysterious (Horstmann & Bischoff 2014).…”
Section: Introductionmentioning
confidence: 88%
“…Photometric observations before the impact revealed that the asteroid was an elongated body in excited rotational state with period of rotation 99.2 s and period of precession 97.0 s (Scheirich et al 2010). By combining various data, the most probable dimensions were estimated to be 6.6 × 3.6 × 2.4 m, mass 40,000 kg, bulk density 1800 kg m −3 , and porosity ∼ 50% (Borovička et al 2015). The impact occurred in Sudan and numerous small meteorites (< 0.4 kg) were found in the desert (Jenniskens et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, every new fireball producing meteorite with precise atmospheric and orbital data gives us invaluable information not only about each particular event but also about its parent body. A detailed inventory of all known instrumentally documented falls is given in the review work Borovička et al, 2015. From the list of all 22 cases (status until end of 2013) it can be seen that meteorites were observed to fall from meteoroids of a wide range of masses, causing fireballs different by orders of magnitude in terms of energy and brightness. At the lower end, there were meteoroids of initial masses of only a few dozens of kg causing fireballs of absolute magnitude of about −10 or even slightly less, such as Bunburra Rockhole (Bland et al, 2009 or Mason Gully (Spurný et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In the list of instrumentally documented falls the most exceptional cases are the heterogeneous falls Almahata Sitta (Jenniskens et al, 2009) and Benešov (Spurný et al, 2014), which revolutionized our view of the structure and composition of small asteroids; the Příbram-Neuschwanstein orbital pair (Ceplecha, 1961 andSpurný et al, 2002), new type of meteorites such as the carbonaceous chondrite Tagish Lake (Brown et al, 2000) or anomalous achondrite Bunburra Rockhole (Bland et al, 2009) and the Chelyabinsk fall, which produced a damaging blast wave Popova et al, 2013). Apart from these cases summarized and in detail described in Borovička et al, 2015, there are two new instrumentally documented meteorite falls observed in 2014. They are closely described in the following two sections.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation